2010
DOI: 10.1186/1758-907x-1-18
|View full text |Cite
|
Sign up to set email alerts
|

MicroR159 regulation of most conserved targets in Arabidopsis has negligible phenotypic effects

Abstract: BackgroundA current challenge of microRNA (miRNA) research is the identification of biologically relevant miRNA:target gene relationships. In plants, high miRNA:target gene complementarity has enabled accurate target predictions, and slicing of target mRNAs has facilitated target validation through rapid amplification of 5' cDNA ends (5'-RACE) analysis. Together, these approaches have identified more than 20 targets potentially regulated by the deeply conserved miR159 family in Arabidopsis, including eight MYB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 49 publications
4
72
1
Order By: Relevance
“…A possible mechanism could involve stimulation of DUO1 turnover via miR159-mediated regulation since the DUO1 transcript contains a functional miR159 binding site (Palatnik et al, 2007). Borges et al (2011) found that miR159a was significantly enriched in sperm cells and miR159-guided cleavage products as well as noncanonical products were detected in wild-type inflorescences and pollen Allen et al, 2010). Furthermore, the DUO1 promoter is sufficient to direct male germline-specific expression, suggesting that miR159-mediated regulation of DUO1 may be restricted to the male germline (Brownfield et al, 2009a).…”
Section: Daz1 and Daz2 Are Required For Sperm Cell Differentiation Anmentioning
confidence: 99%
“…A possible mechanism could involve stimulation of DUO1 turnover via miR159-mediated regulation since the DUO1 transcript contains a functional miR159 binding site (Palatnik et al, 2007). Borges et al (2011) found that miR159a was significantly enriched in sperm cells and miR159-guided cleavage products as well as noncanonical products were detected in wild-type inflorescences and pollen Allen et al, 2010). Furthermore, the DUO1 promoter is sufficient to direct male germline-specific expression, suggesting that miR159-mediated regulation of DUO1 may be restricted to the male germline (Brownfield et al, 2009a).…”
Section: Daz1 and Daz2 Are Required For Sperm Cell Differentiation Anmentioning
confidence: 99%
“…This technology is still expensive, but has the advantage of validating predicted miRNA targets, in a large scale, before proceeding to the time consuming functional characterization of the miRNA-target interaction. As discussed by Allen et al (2010) working with the conserved miR159, there may be an overestimation of miRNA regulatory complexity promoted by methodologies such as the 5′-RACE. In fact, they showed that loss-of-function studies are relevant for identification of key miRNA-target relationships, in alignment with quantitative degradome approaches that will mostly detect strong regulatory interactions.…”
Section: Functional Characterization Of Srnas and Their Targets In Sementioning
confidence: 99%
“…For transcriptome experiments, RNA was isolated using Trizol reagent (Life Technologies) using a procedure adapted from Allen et al (2010). Briefly, up to 100 mg of snap-frozen tissue was ground then lysed in 1 mL of Trizol with gentle agitation.…”
Section: Rna Isolation and Quality Assessmentmentioning
confidence: 99%